Development of Interactive Flipbook Media to Enhance Science Literacy Based on Sustainable Lifestyle in Elementary Schools - Winny Sunfriska br Limbong; Taruli Marito Silalahi; Muhammad Fadli (Journal La Edusci, 2026)
This study is motivated by the urgency of rapid digitalization in the 21st century, which necessitates the development of innovative, interactive, and contextual learning media. The purpose of this research is to develop a flipbook-based learning medium that integrates sustainable lifestyle values to enhance science literacy among elementary school students. The study employed the ADDIE development model comprising Analysis, Design, Development, Implementation, and Evaluation through stages that included needs analysis, media design, product development, classroom implementation, and evaluation. Data were collected through surveys, interviews, observations, and tests involving fifth-grade students from eight elementary schools in Medan City. The results indicate that the developed flipbook met the criteria of validity, practicality, and effectiveness based on expert validation and classroom implementation tests. The flipbook, which incorporates learning materials, simulations, evaluations, animations, and interactive visuals, effectively stimulates students’ learning motivation and improves their science literacy skills. A novel finding of this study is the integration of science literacy with sustainable lifestyle values, which not only introduces scientific concepts but also instills positive habits for environmental preservation and social responsibility from an early age. The discussion emphasizes that the use of flipbook media can serve as an innovative alternative for teachers in science learning at the elementary level. This research produces an empirically tested flipbook medium and a teacher’s instructional guide, thereby contributing to the advancement of educational science and the practice of sustainable education.